Ментовская работа: повести / Данил Корецкий - Корецкий Данил Аркадьевич (Серия "Чёрная кошка", 1997)
Экземпляры: ф. 2 (20120122) / Инвентарный номер: 97757 / Цена: 50.00 / Авт.знак: К 66 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6